2015
DOI: 10.1063/1.4933006
|View full text |Cite
|
Sign up to set email alerts
|

Dust-acoustic waves modulational instability and rogue waves in a polarized dusty plasma

Abstract: The polarization force-induced changes in the dust-acoustic waves (DAWs) modulational instability (MI) are examined. Using the reductive perturbation method, the nonlinear Schrödinger equation that governs the MI of the DAWs is obtained. It is found that the effect of the polarization term R is to narrow the wave number domain for the onset of instability. The amplitude of the wave envelope decreases as R increases, meaning that the polarization force effects render weaker the associated DA rogue waves. The la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The observation of these higher-(second-) order rogue waves (RWs) has been verified in laboratory experiment including theoretical investigation [37,38]. Numerous investigations of dust acoustic rogue waves have been reported in different plasma environments [43][44][45][46][47][48][49][50]. Singh and Saini [49] have observed that polarization force controls the MI domain of DA waves in a superthermal dusty plasma.…”
Section: Introductionmentioning
confidence: 84%
“…The observation of these higher-(second-) order rogue waves (RWs) has been verified in laboratory experiment including theoretical investigation [37,38]. Numerous investigations of dust acoustic rogue waves have been reported in different plasma environments [43][44][45][46][47][48][49][50]. Singh and Saini [49] have observed that polarization force controls the MI domain of DA waves in a superthermal dusty plasma.…”
Section: Introductionmentioning
confidence: 84%
“…To study the MI of DAWs, we will derive the NLSE by employing the standard multiple scale (reductive perturbation) technique . Let A be the state (column) vector ( n d , u d , ϕ ) T , describing the system's state at a given position x and instant t. We shall consider small deviations from the equilibrium state A (0) = (1, 0, 0) T by taking …”
Section: Derivation Of Nlsementioning
confidence: 99%
“… A=A()0+ϵA()1+ϵ2A()2+=A()0+false∑n=1ϵnA()n, where ϵ ≪ 1 is a smallness parameter. In the standard multiple scale (reductive perturbation) technique, the stretched (slow) space and time variables are commonly used by many authors as follows: ξ=ϵxvgt,τ=ϵ2t, where v g is the group velocity in the x direction. We assume that all perturbed states depend on the fast scales via the phase θ 1 = kx − ωt only, while the slow scales enter the argument of the l th harmonic amplitude Al()n, which is allowed to vary along x , A()n=false∑l=Al()nξτeilkxωitalict. …”
Section: Derivation Of Nlsementioning
confidence: 99%
See 1 more Smart Citation
“…Rogue wave is a complex, rare, short‐lived, and high energetic pulse, which is an interesting research topic for the plasma physicists. Therefore, researchers have theoretically investigated the properties of rogue waves in many plasma systems [6,10,39–43] . Sabry et al [42] have reported the propagation properties of IARWs in an unmagnetized plasma medium with warm ions, electrons, and positrons and analysed that the IARWs become suddenly high energetic pulse around the critical wave number ( k c ) and later decrease with increasing the k c .…”
Section: Introductionmentioning
confidence: 99%